2017
DOI: 10.1002/gps.4698
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery calcification and cognitive function: cross‐sectional results from the ELSA‐Brasil study

Abstract: Higher CAC was weakly associated with poorer performance in an executive function test in a large sample from the Brazilian Longitudinal Study of Adult Health. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Three cross-sectional studies 17 , 34 , 35 ) and two longitudinal cohort studies 36 , 37 ) examined the cross-sectional association between CAC and cognitive scores for different cognitive domains. Increasing severity of CAC was associated with worse performance of episodic memory 34 , 36 ) , semantic fluency 36 ) , executive function 17 , 34 36 ) , and global cognition 34 , 37 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Three cross-sectional studies 17 , 34 , 35 ) and two longitudinal cohort studies 36 , 37 ) examined the cross-sectional association between CAC and cognitive scores for different cognitive domains. Increasing severity of CAC was associated with worse performance of episodic memory 34 , 36 ) , semantic fluency 36 ) , executive function 17 , 34 36 ) , and global cognition 34 , 37 ) .…”
Section: Resultsmentioning
confidence: 99%
“…In light of previous literature, strict invariance model misfit resulting in not equivalent error indicator variances for the model was expected. Although we attempted to adjust for other sociodemographic variables, considering the diversity of the ELSA-Brasil sample, heterogeneity, and some clinical characteristics (e.g., cardiovascular risk factors and diseases) might have contributed to not achieving strict invariance (Kemp, Koenig, et al, 2016; Kemp, López, et al, 2016; Suemoto et al, 2018; Suemoto, Bittencourt, Santos, Benseñor, & Lotufo, 2017). We decided not to control for all possible causes to avoid potential misinterpretations when multiple cofounders are considered, which may lead to a lack of reproducibility in the present findings (Westreich & Greenland, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between CAC and dementia is controversial, some researchers support the idea that the risk of dementia is associated with the CAC score (Kuller et al, 2016;Fujiyoshi et al, 2017), while some are negative (Lee et al, 2016). A cross-section study conducted by Suemoto et al suggested that higher CAC is faintly correlated with inferior executive function (Suemoto et al, 2017). The differences among the various experimental results should be noted.…”
Section: As Biomarkersmentioning
confidence: 99%